Effects of a novel phosphorus–nitrogen flame retardant on rosin-based rigid polyurethane foams. (October 2015) - Zhang, Meng; Luo, Zhenyang; Zhang, Jinwen; Chen, Shuigen; Zhou, Yonghong
Abstract: A novel phosphorus-nitrogen flame retardant (DOPO-BA) was synthesized from the condensation reaction of benzaldehyde, aniline and 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO). The structure of DOPO-BA was characterized by Fourier transform infrared spectrometry (FTIR), 1 H NMR, 31 P NMR, elemental analysis and thermogravimetric analysis (TGA). DOPO-BA was used as a flame retardant in the preparation of rosin-based rigid polyurethane foams (RPUFs). The effects of DOPO-BA addition on the mechanical, thermal, and flame-retardant properties of RPUF were investigated. The morphology of DOPO-BA filled RPUFs was characterized by scanning electron microscope (SEM). The results show that DOPO-BA rendered RPUF good physical, thermal stability and flame-retardant properties. Limiting oxygen index (LOI) value of RPUF containing 20 wt% DOPO-BA increased to 28.1% from 20.1% of the RPUF without DOPO-BA.